Extending magnifying NBI diagnosis of intestinal metaplasia in the stomach: the white opaque substance marker - Kanemitsu, Takao; Yao, Kenshi; Nagahama, Takashi; Imamura, Kentaro; Fujiwara, Shoko; Ueki, Toshiharu; Chuman, Kenta; Tanabe, Hiroshi; Atsuko, Ota; Iwashita, Akinori; Shimokawa, Toshio; Uchita, Kunihisa; Kanesaka, Takashi (Endoscopy, 2017)
Background and aims Intestinal metaplasia (IM) of the stomach is associated with an increased risk of differentiated gastric cancer. While it is important to diagnose IM endoscopically, it can be difficult to observe by white-light endoscopy. In magnifying endoscopy with narrow-band imaging (M-NBI) of the stomach, a light-blue crest (LBC) is widely known to be a useful marker in the endoscopic diagnosis of IM. However, IM that exhibits only white opaque substance (WOS) without an LBC can also occur. The aim of this study was to elucidate whether the presence of WOS on M-NBI of the stomach could serve as a marker of IM in the same way that an LBC does.Methods The subjects were 40 consecutive patients who underwent M-NBI between July and December 2014. The primary endpoint in this study was to evaluate the diagnostic performance of M-NBI for histologically observed IM in WOS- and LBC-positive mucosa. Results The sensitivity and specificity of WOS for histologically diagnosed IM were 50.0 % (95 % confidence interval [CI] 40.0 % – 50.0 %) and 100.0 % (95 %CI 85.0 % – 100.0 %), respectively. Meanwhile, the sensitivity and specificity of LBC were 62.5 % (95 %CI 51.1 % – 65.9 %) and 93.8 % (95 %CI 76.7 % – 98.9 %), respectively. The sensitivity and specificity of WOS and/or LBC (WOS positive and LBC positive, WOS positive and LBC negative, or WOS negative and LBC positive) for histologically diagnosed IM were 87.5 % (95 %CI 76.9 % – 90.9 %) and 93.8 % (95 %CI 77.9 % – 98.9 %), respectively.Conclusions LBC and WOS are both useful markers for endoscopic diagnosis of IM. Combining both markers improves the sensitivity.Clinical trial number: UMINCTR000014453.